The Use of Flashcards Monopoly to Facilitate Elementary Students’ Learning English Vocabulary - Sri Melani; prasetya, willy (Universitas PGRI Yogyakarta, 2024)
In learning English, using appropriate methods to support learning is highly considered, especially for young learners. It helps increase students' motivation and engagement in learning, and students can more easily understand English learning. In this article, the teaching practice implemented the game-based learning method through flashcards monopoly. This article aims to facilitate the learning of English vocabulary for elementary students who have never studied English. The article data was obtained through the implementation of teaching practice which was carried out for 5 months (February-June). Moreover, the teaching practice was carried out in grade 4 at one of the public elementary schools in the Sukabumi district, Indonesia. Students acquire English vocabulary and easily understand and remember it through the flashcard Monopoly game. Students are very interested in learning, actively participate, and are brave enough to mention new vocabulary, the use of flashcards monopoly also motivates and engages students in learning English.